Plasma Epstein-Barr virus DNA for pediatric Burkitt lymphoma diagnosis, prognosis, and response assessment in Malawi - Westmoreland, Katherine D. (Int J Cancer, 2017)
Point-of-care tools are needed in sub-Saharan Africa (SSA) to improve pediatric Burkitt lymphoma (BL) diagnosis and treatment. We evaluated plasma Epstein-Barr virus (pEBV) DNA as a pediatric BL biomarker in Malawi. Prospectively enrolled children with BL were compared to classical Hodgkin lymphoma (cHL) and non-lymphoma diagnoses. Pediatric BL patients received standardized chemotherapy and supportive care. pEBV DNA was measured at baseline, mid-treatment, and treatment completion. Of 121 assessed children, pEBV DNA was detected in 76/88 (86%) with BL, 16/17 (94%) with cHL, and 2/16 (12%) with non-lymphoma, with proportions higher in BL versus non-lymphoma (p<0.001) and similar in BL versus cHL (p=0.69). If detected, median pEBV DNA was 6.1 log(10)copies/mL for BL, 4.8 log(10)copies/mL for cHL, and 3.4 log(10)copies/mL for non-lymphoma, with higher levels in BL versus cHL (p=0.029), and a trend toward higher levels in BL versus non-lymphoma (p=0.062). pEBV DNA declined during treatment in the cohort overall and increased in several children before clinical relapse. Twelve-month overall survival was 40% in the cohort overall, and for children with baseline pEBV detected, survival was worse if baseline pEBV DNA was ≥6 log(10)copies/mL versus <6 log(10)copies/mL (p=0.0002), and also if pEBV DNA was persistently detectable at mid-treatment versus undetectable (p=0.041). Among children with baseline pEBV DNA detected, viremia was the only significant risk factor for death by 12 months in multivariate analyses (adjusted hazard ratio 1.35 per log(10)copies/mL, 95% CI 1.04–1.75, p=0.023). Quantitative pEBV DNA has potential utility for diagnosis, prognosis, and response assessment for pediatric BL in SSA.